Seroprevalence and Risk Factor Analysis of Hog Cholera Disease at Small Farm in Deli Serdang Regency - Soula Wulandary; Ma'ruf Tafsin; Faisal (Indonesian Journal of Agricultural Research, 2021)
Hog cholera is an epizootic viral diseases that attack pig. The disease is caused by Pestivirus C which belongs to the genus Pestivirus and the family Flaviviridae. Information about the prevalence and risk factors of hog cholera incidence in North Sumatra and especially in the Deli Serdang Regency became the basis for this research. This study aims to find out the prevalence and factors associated with seropositive hog cholera in Deli Serdang Regency. Samples were taken using a random sample technique with a simple random type. A total of 196 blood samples were collected from 8 sub-districts, 11 villages, and 54 farms in the Deli Serdang district. Animal and breeder data were collected with questionnaires to determine the incidence and causative factors of hog cholera seropositive. Data analysed using univariable and multivariable logistical regression tests to determine the association between hog cholera infection and risk factors. The results showed that the prevalence of Hog Cholera seroposive events at the agricultural level was 9% (5/54) and the individual rate was 10% (20/196). The results showed that the prevalence of Hog Cholera seroposive events at the agricultural level was 9% (5/54) and the individual rate was 10% (20/196). The conclusion of this research that the risk factors associated with pig cholera were landrace pigs (OR 14,28, 95% CI: 1.04-195) were more likely to have seropositif than other breeds and vaccination (OR 0.0048, 95% CI: 0.004-0.498) potential factors reducing hog cholera infection.